(3ejOGf GdaQSGf aj aQhY GdTGaYjIs - (3eMeO Hf Nda Hf cGed Hf YWGA Gddg , TeS GdOjf CHh YHO Gddg GdZRj GdTGaYj,J (B770 (3g` s
(3ChdgG (B:s
(3Ghd cJGH GMjGA GdehGJ s
(3BNQgG (B:s
(3BNQ cJGH GdMVGfI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B285s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1916s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1141) s
Keywords: (3Gdabg GdTGaYjs